2009
DOI: 10.1007/s11069-009-9403-2
|View full text |Cite
|
Sign up to set email alerts
|

Landslide hazard zonation in high risk areas of Rethymno Prefecture, Crete Island, Greece

Abstract: The central part of Rethymnon Prefecture, Crete Island, suffers from severe landslide phenomena because of its geological and geomorphological settings alternated by the human activities. The main landslide preparatory and triggering causal factors are considered to be the ground conditions (lithology), geomorphological processes (fluvial erosion, etc.), and the man-made actions (excavations, loading etc.). The purpose of this study is to develop a decision support and continuous monitoring system of the area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 48 publications
1
72
0
4
Order By: Relevance
“…Stereoscopic interpretation of pan-sharpened images (e.g. Nichol et al, 2006, Kouli et al, 2010 and automatic pixel-and object-oriented classification methods (e.g, Martha et al, 2010;Mondini et al, 2011;Holbling et al, 2012) showed potential for landslide mapping. Change detection based on temporal variations of landscape spectral properties (pre-and post-landslide event) are particularly effective for updating landslide affected areas (e.g.…”
Section: Monoscopic And/or Stereoscopic Analysis Of Panchromatic Multmentioning
confidence: 99%
“…Stereoscopic interpretation of pan-sharpened images (e.g. Nichol et al, 2006, Kouli et al, 2010 and automatic pixel-and object-oriented classification methods (e.g, Martha et al, 2010;Mondini et al, 2011;Holbling et al, 2012) showed potential for landslide mapping. Change detection based on temporal variations of landscape spectral properties (pre-and post-landslide event) are particularly effective for updating landslide affected areas (e.g.…”
Section: Monoscopic And/or Stereoscopic Analysis Of Panchromatic Multmentioning
confidence: 99%
“…These methods have different characteristics and adaptability for various environmental conditions of different regions (Tangestani 2009;Mohammady et al 2012;Ozdemir and Altural 2013). At the same time, GIS and RS technologies have comprehensively been used in the landslide susceptibility study Lan et al 2002Lan et al , 2004Kouli et al 2010;Niu et al 2012). All landslide susceptibility assessment methods, despite methodological and operational differences, are based on the common assumption that the future landslides will be likely to occur under the same conditions that induce past landslides (Clerici et al 2006;Aleotti and Chowdhury 1999;Guzzetti et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The interplay between the database system and Geographical Information System was established with the defined coordinates of the locations of existing landslide occurrences. After modifications, 979 landslide occurrences, which occurred between 1952 and 2012, were recorded and digitally stored [21,25,33,34,[45][46][47][48][49]. The spatial distribution of the recorded occurrences and the evaluation of the processed data led to the compilation of a landslide inventory map of Western Thessaly basin (Figure 4).…”
Section: Methodsmentioning
confidence: 99%